Synchronous online learning and career readiness in higher education: student perceptions, challenges, and solutions - Lukashe, Mihlali; Chigbu, Bianca Ifeoma; Umejesi, Ikechukwu (Frontiers in Education, 2024)
Synchronous Online Learning (SOL) environments have rapidly transformed the educational landscape. However, there is limited research on their efficacy in equipping students with the necessary skills to succeed in the workforce, particularly in developing essential professional skills like digital literacy, interpersonal communication, and practical experience. This study explores how SOL impacts students’ readiness for the workforce and the development of these critical skills. The research employed a qualitative methodology involving in-depth interviews with 27 third- and fourth-year students from a South African university. Purposive sampling was used to capture diverse experiences regarding SOL and its influence on professional skill development. Thematic analysis was performed to identify critical patterns and insights from the interviews. Findings reveal that SOL environments effectively enhance students’ technical skills and digital adaptability, essential for navigating a digital workforce. However, SOL is inadequate in developing interpersonal skills and providing practical, hands-on experiences. Students reported a lack of networking opportunities and expressed concerns about their preparedness for the demands of real-world employment, particularly in fields requiring strong interpersonal skills and practical experience. The study highlights the need for educational innovations that combine the benefits of digital learning with comprehensive skill development strategies, particularly in soft skills and experiential learning.